Perbedaan Tinggi Processus Coronoid dalam Identifikasi Jenis Kelamin Ditinjau dari Radiograf Panoramik - Farizka, Intan; Zahra Nur Aulia, Adinda (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Sex determination is a fundamental aspect of forensic dentistry. Mandibular sexual dimorphism, particularly in the height of the coronoid process, has been extensively researched as a potential biological marker. The aim of this literature review is to analyze findings from various studies that evaluate the difference in coronoid process height between males and females using panoramic radiographs. Literature Review: Panoramic radiography, or orthopantomography (OPG), is often used in forensic odontology as an identification because the method is simple and proven to be accurate in measuring anatomical structures. The coronoid process is one of the mandibular characteristics commonly assessed for its potential role in sex determination. This pointed projection provides an attachment point for the temporalis muscle and is one of the two processes that form the anterior part of the ramus. The height of the coronoid process is one of the most significant parameters of the mandibular ramus for determining sexual dimorphism. Studies that include publications and research articles on the use of panoramic radiographs to identify differences in coronoid process height between males and females have shown significant results. Conclusion: Based on this literature review, measuring the height of the coronoid process on panoramic radiographs is a valid and relatively accurate method for predicting sex. The sexual dimorphism of this structure can be utilized in forensic dentistry as a supporting tool for identification. However, further research is recommended to consider ethnic variations and to develop specific population-based data points to improve precision.